Lightweight, low-shrinkage and high-strength sea sand mortar and preparation method thereof

By combining hollow microbeads and proppants, sulfoaluminate cement and sea sand and other materials, the problems of low strength and large shrinkage of traditional cement mortar are solved, and lightweight, low shrinkage and high strength sea sand mortar is achieved, which is suitable for construction. , save freshwater resources.

CN116217198BActive Publication Date: 2024-12-31SHENZHEN AEROSPACE NEW MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310361737.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-29
Publication Date
2024-12-31
Estimated Expiration
2043-03-29

AI Technical Summary

Technical Problem

Traditional cement mortar has low strength, heavy capacity and will experience large shrinkage after hardening, making it difficult to meet the needs of lightweight, low shrinkage, high strength and rapid repair in construction projects.

Method used

The combination of hollow microbeads of different particle sizes and proppants is used to form a dense structure, combining sulfur aluminate cement and sea sand as aggregates, reducing the bulk weight of the mortar and improving strength, while increasing through fly ash and polypropylene fibers. Flowability and crack resistance.

Benefits of technology

It has achieved lightweight, low shrinkage and high strength sea sand mortar, with a volume weight reduced by 15%-25%, a strength of more than 80MPa, good fluidity, suitable for construction, and saving fresh water resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116217198B_ABST
    Figure CN116217198B_ABST
Patent Text Reader

Abstract

The present application provides a light, low-shrinkage, high-strength sea sand mortar and a preparation method thereof, wherein the sea sand mortar comprises, by mass, 250-350 parts of silicate cement, 300-480 parts of sulphoaluminate cement, 100-200 parts of fly ash, 50-100 parts of silica ash, 100-200 parts of composite hollow microspheres, 200-300 parts of composite proppants, 300-450 parts of sea sand, 5-15 parts of admixtures, and 200-260 parts of water. By using three hollow microspheres of different particle sizes as lightweight aggregates and three proppants of different particle sizes as supports, the two are compounded to form a dense pile structure, which can reduce the bulk density of the mortar and improve the strength of the mortar; sulphoaluminate cement has good adjustable expansion properties, and by using sulphoaluminate cement as a cementitious material, the shrinkage of the mortar can be fully compensated; by using sea sand instead of river sand as aggregate, river sand and a large amount of fresh water resources can be saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building mortar, and in particular to a lightweight, low-shrinkage, high-strength sea sand mortar and a preparation method thereof. Background Art

[0002] Mortar is a common construction material in the field of construction engineering. It can be used for foundation grouting, plastering, construction joint embedding, repair and reinforcement, etc. With the development of society, people have put forward higher performance requirements for mortar materials, such as environmental protection and energy saving, light weight, high strength, durability, low shrinkage, crack resistance, impermeability, fire resistance, sound insulation, etc.

[0003] Traditional cement mortar can no longer meet actual engineering needs in some areas due to its low strength, high bulk density, and large shrinkage after hardening. For example, traditional cement mortar is difficult to fill densely when used for grouting, and is prone to cracking and falling off when used for plastering, resulting in a deterioration in the wall decoration effect. When used for repairs, gaps will appear again between the repair material and the structure, affecting the repair effect. In addition, traditional cement mortar has the disadvantages of slow coagulation and hardening and low early strength when used for repairs, which will extend the construction period of the repair project and make it difficult to meet the needs of rapid repairs in certain projects. Summary of the invention

[0004] In view of the above problems, the present application is proposed to provide a lightweight, low-shrinkage, high-strength sea sand mortar and a preparation method thereof that overcomes the above problems or at least partially solves the above problems, comprising:

[0005] A lightweight, low-shrinkage, high-strength sea sand mortar comprises, by weight, 250-350 parts of silicate cement, 300-480 parts of sulphoaluminate cement, 100-200 parts of fly ash, 50-100 parts of silica fume, 100-200 parts of composite hollow microspheres, 200-300 parts of composite proppants, 300-450 parts of sea sand, 5-15 parts of admixtures and 200-260 parts of water; wherein the composite hollow microspheres comprise hollow microspheres of at least three different particle sizes; and the composite proppants comprise proppants of at least three different particle sizes.

[0006] Preferably, the composite hollow microbeads include first hollow microbeads with a particle size of 75-100 μm, second hollow microbeads with a particle size of 100-150 μm and third hollow microbeads with a particle size of 150-250 μm, wherein the mass ratio of the first hollow microbeads, the second hollow microbeads and the third hollow microbeads is (1-3): (4-6): (2-4).

[0007] Preferably, the composite hollow microspheres are sintered at 1400°C.

[0008] Preferably, the composite proppant comprises a first ceramsite with a mesh size of 20-40, a second ceramsite with a mesh size of 40-70 and a third ceramsite with a mesh size of 70-140, wherein the mass ratio of the first ceramsite, the second ceramsite and the third ceramsite is (1-3): (3-5): (3-5).

[0009] Preferably, the mass proportion of spherical particles in the fly ash is greater than 95%, wherein the mass proportion of the spherical particles with a particle size of ≤1 μm is greater than 90%.

[0010] Preferably, the admixture includes a water reducer, a defoamer, a retarder and a thickener; the water reducer includes a powder water reducer and a liquid water reducer, wherein the mass ratio of the powder water reducer to the liquid water reducer is (1-3): (14-16).

[0011] Preferably, the invention further comprises, by weight, 20-50 parts of gypsum.

[0012] Preferably, the invention further comprises, by weight, 5-12 parts of polypropylene fibers.

[0013] Preferably, the polypropylene fiber has a length of 15-25 mm, a tensile strength of >500 MPa, and an elastic modulus of >4500 MPa.

[0014] A method for preparing the sea sand mortar as described above comprises:

[0015] Put the silicate cement, the sulphoaluminate cement, the fly ash, the silica fume, the composite hollow microspheres, the composite proppant, the sea sand and the dry components of the admixture into a dry mortar mixer, and stir at a constant speed for 15-20 minutes to obtain a mixed dry material;

[0016] Put the mixed dry materials into a concrete mixer, stir at a constant speed for 1-2 minutes, add the aqueous component in the admixture and the water, stir at a constant speed for 5-8 minutes, and obtain a mixed slurry;

[0017] The mixed slurry is vibrated into shape and cured to obtain the sea sand mortar.

[0018] This application has the following advantages:

[0019] In the embodiments of the present application, relative to the problems of low strength and large bulk density of traditional cement mortar, the present application provides a solution of using a compound of hollow microspheres and proppants to reduce the bulk density of the mortar while improving the strength of the mortar, specifically: "A lightweight, low-shrinkage, high-strength sea sand mortar, comprising, by mass: 250-350 parts of silicate cement, 300-480 parts of sulphoaluminate cement, 100-200 parts of fly ash, 50-100 parts of silica ash, 100-200 parts of compound hollow microspheres, 200-300 parts of compound proppants, 300-450 parts of sea sand, 5-15 parts of admixtures and 200-260 parts of water; wherein the compound hollow microspheres include at least three hollow microspheres of different particle sizes; the compound proppants include at least three proppants of different particle sizes". By using at least three hollow microspheres of different particle sizes as lightweight aggregates and at least three proppants of different particle sizes as supports, the two are compounded to form a dense pile structure, which can reduce the bulk density of the mortar (the bulk density of the sea sand mortar is 1500-1700kg / m 3 The bulk density of traditional cement mortar is about 2000kg / m 3 , that is, the bulk density of the sea sand mortar is reduced by about 15%-25% compared with the traditional cement mortar), and the strength of the mortar is improved (the strength of the sea sand mortar reaches more than 80MPa); the sulphoaluminate cement has good adjustable expansion performance. By adopting the sulphoaluminate cement as a cementitious material, the shrinkage of the mortar can be fully compensated, and the strength of the mortar can be improved; by adopting the sea sand instead of river sand as aggregate, natural river sand can be saved, and the sea sand does not need to be washed with fresh water, which can save a lot of fresh water resources; in addition, the fly ash, the hollow microspheres and the proppant are all round spheres, which can increase the fluidity of the mortar and facilitate construction, and the hollow microspheres are calcined at high temperature, and their surface is relatively smooth, similar to glass, which can further reduce the viscosity of the mortar, increase the fluidity, and facilitate construction. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the description of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0021] Figure 1 This is a step flow chart of a method for preparing sea sand mortar provided in one embodiment of the present application. DETAILED DESCRIPTION

[0022] In order to make the objects, features and advantages of the present application more obvious and understandable, the present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0023] In one embodiment of the present application, a lightweight, low-shrinkage, high-strength sea sand mortar is provided, which includes, by mass: 250-350 parts of silicate cement, 300-480 parts of sulphoaluminate cement, 100-200 parts of fly ash, 50-100 parts of silica fume, 100-200 parts of composite hollow microspheres, 200-300 parts of composite proppant, 300-450 parts of sea sand, 5-15 parts of admixture and 200-260 parts of water; wherein the composite hollow microspheres include hollow microspheres of at least three different particle sizes; the composite proppant includes proppant of at least three different particle sizes.

[0024] In the embodiments of the present application, relative to the problems of low strength and large bulk density of traditional cement mortar, the present application provides a solution of using a compound of hollow microspheres and proppants to reduce the bulk density of the mortar while improving the strength of the mortar, specifically: "A lightweight, low-shrinkage, high-strength sea sand mortar, comprising, by mass: 250-350 parts of silicate cement, 300-480 parts of sulphoaluminate cement, 100-200 parts of fly ash, 50-100 parts of silica ash, 100-200 parts of compound hollow microspheres, 200-300 parts of compound proppants, 300-450 parts of sea sand, 5-15 parts of admixtures and 200-260 parts of water; wherein the compound hollow microspheres include at least three hollow microspheres of different particle sizes; the compound proppants include at least three proppants of different particle sizes". By using at least three hollow microspheres of different particle sizes as lightweight aggregates and at least three proppants of different particle sizes as supports, the two are compounded to form a dense pile structure, which can reduce the bulk density of the mortar (the bulk density of the sea sand mortar is 1500-1700kg / m 3 The bulk density of traditional cement mortar is about 2000kg / m 3 , that is, the bulk density of the sea sand mortar is reduced by about 15%-25% compared with the traditional cement mortar), and at the same time the strength of the mortar is improved (the strength of the sea sand mortar reaches more than 80MPa); the sulphoaluminate cement has good adjustable expansion performance, and by adopting the sulphoaluminate cement as the cementitious material, the shrinkage of the mortar can be fully compensated; in addition, by adopting the sea sand instead of river sand as aggregate, natural river sand can be saved, and the sea sand does not need to be flushed with fresh water, which can save a lot of fresh water resources.

[0025] Next, a lightweight, low-shrinkage, high-strength sea sand mortar in this exemplary embodiment will be further described.

[0026] In this embodiment, the composite hollow microbeads include first hollow microbeads with a particle size of 75-100 μm, second hollow microbeads with a particle size of 100-150 μm, and third hollow microbeads with a particle size of 150-250 μm, wherein the mass ratio of the first hollow microbeads, the second hollow microbeads, and the third hollow microbeads is (1-3): (4-6): (2-4), preferably 2:5:3.

[0027] In this embodiment, the wall thickness of the composite hollow microspheres is 8%-15% of the diameter, and the floating rate is ≥98%; the bulk density of the composite hollow microspheres is 350-600 kg / m 3 , apparent density is 600-850kg / m 3 .

[0028] In this embodiment, the composite hollow microspheres are sintered at 1400°C. Specifically, the composite hollow microspheres include SiO 2 、Al 2 O 3 and Fe 2 O 3 , wherein the SiO 2 The mass proportion of Al 2 O 3 The mass proportion of Fe is 25-45%, 2 O 3 The composite hollow microspheres are calcined at high temperature, and have a relatively smooth surface, similar to glass, which can reduce the viscosity of the mortar, increase fluidity, and facilitate construction.

[0029] In this embodiment, the composite proppant includes a first ceramsite with a mesh size of 20-40, a second ceramsite with a mesh size of 40-70, and a third ceramsite with a mesh size of 70-140, wherein the mass ratio of the first ceramsite, the second ceramsite and the third ceramsite is (1-3): (3-5): (3-5), preferably 2:4:4.

[0030] In this embodiment, the apparent density of the composite proppant is 1450-1850 kg / m 3 .

[0031] In this embodiment, the silicate cement is PⅡ52.5 cement, which has the characteristics of high strength, impermeability and corrosion resistance.

[0032] In this embodiment, the mass proportion of spherical particles in the fly ash is greater than 95%, wherein the mass proportion of spherical particles with a particle size of ≤1 μm is greater than 90%. By using the fly ash whose main component is spherical particles, the fly ash, the hollow microspheres and the proppant are all spherical structures, so that the mortar has good fluidity and is easy to construct.

[0033] In this embodiment, the SiO 2 The mass proportion is ≥96%; the average particle size of the silica ash is 0.1-0.15μm, and the 7d activity index is ≥110%.

[0034] In this embodiment, the fineness modulus of the sea sand is 2.5 and the particle size is less than 5 mm.

[0035] In this embodiment, the admixture includes a water reducer, a defoamer, a retarder and a thickener; the water reducer includes a powder water reducer and a liquid water reducer, wherein the mass ratio of the powder water reducer to the liquid water reducer is (1-3): (14-16), preferably 2: 15. Specifically, the powder water reducer and the liquid water reducer are both polycarboxylate water reducers, the model of the powder water reducer is Sika 325C, and the model of the liquid water reducer is Hongqiang JSM3; the defoamer is a polyether modified polysiloxane defoamer, model P803; the retarder is tartaric acid; the model of the thickener is T400.

[0036] In this embodiment, the mortar further comprises 20-50 parts by weight of gypsum, which has a fast setting and hardening speed, has a slight expansion property after hydration, has a stable volume after hardening, and is not prone to shrinkage and cracking. By adding the gypsum, large shrinkage can be avoided after the mortar hardens.

[0037] In this embodiment, the mortar further comprises 5-12 parts of polypropylene fibers by weight. The polypropylene fibers can resist the shrinkage of the mortar and improve the water retention of the mortar. The polypropylene fibers are evenly dispersed in the mortar matrix after stirring, which can inhibit the sinking of particles in the mortar, thereby reducing the capillary channels formed by the overflow of water in the mortar, delaying the generation of cracks and controlling the development of cracks, and at the same time improving the strength of the mortar.

[0038] In this embodiment, the length of the polypropylene fiber is 15-25 mm, the tensile strength is greater than 500 MPa, and the elastic modulus is greater than 4500 MPa. By using short fibers, it is easy to evenly disperse in the mortar matrix after stirring, while reducing the influence on the bulk density of the mortar.

[0039] Reference Figure 1 In one embodiment of the present application, a method for preparing the sea sand mortar as described above is also provided, comprising:

[0040] S110, putting the dry components of the silicate cement, the sulphoaluminate cement, the fly ash, the silica fume, the composite hollow microspheres, the composite proppant, the sea sand and the admixture into a dry mortar mixer, and stirring at a constant speed for 15-20 minutes to obtain a mixed dry material;

[0041] S120, putting the mixed dry materials into a concrete mixer, stirring at a constant speed for 1-2 minutes, adding the aqueous component in the admixture and the water, stirring at a constant speed for 5-8 minutes, to obtain a mixed slurry;

[0042] S130, vibrating the mixed slurry into shape and curing it to obtain the sea sand mortar.

[0043] Next, a method for preparing the sea sand mortar as described above in this exemplary embodiment will be further described.

[0044] As described in step S110, the dry components of the silicate cement, the sulphoaluminate cement, the fly ash, the silica fume, the composite hollow microspheres, the composite proppant, the sea sand and the admixture are put into a dry mortar mixer and stirred at a uniform speed for 15-20 minutes to obtain a mixed dry material.

[0045] The silicate cement, the sulphoaluminate cement, the fly ash, the silica fume, the composite hollow microspheres, the composite proppant, the sea sand and the powder water reducing agent (in some embodiments, the gypsum may also be included) are placed in a dry mortar mixer and stirred at a constant speed for 15-20 minutes to obtain the mixed dry material.

[0046] As described in step S120, the mixed dry materials are put into a concrete mixer and stirred at a constant speed for 1-2 minutes, and the aqueous component in the admixture and the water are added and stirred at a constant speed for 5-8 minutes to obtain a mixed slurry.

[0047] The mixed dry materials are placed in a concrete mixer and stirred at a constant speed for 1-2 minutes. The liquid water reducing agent, the defoaming agent, the retarder, the thickener and the water are added while stirring, and stirred at a constant speed for 5-8 minutes (in some embodiments, after completing the above steps, the polypropylene fiber can also be slowly added while stirring, and stirred at a constant speed for 2-3 minutes) to obtain the mixed slurry.

[0048] As described in step S130, the mixed slurry is vibrated into shape and cured to obtain the sea sand mortar.

[0049] A vibrator is used to pump up and down in the mixed slurry (insert quickly and pull out slowly, arrange the insertion points evenly, move point by point, and proceed sequentially) to make the mixed slurry dense and uniform, and then cover and water it within 12 hours. The number of watering times should be able to keep the mixed slurry in a moist state. The curing time is not less than 7 days to obtain the sea sand mortar.

[0050] The following are specific embodiments of the present application:

[0051] Embodiment 1

[0052] Weigh 325 parts of the silicate cement, 450 parts of the sulphoaluminate cement, 120 parts of the fly ash, 90 parts of the silica fume, 25 parts of the gypsum, 150 parts of the composite hollow microspheres, 210 parts of the composite proppant, 400 parts of the sea sand, 2 parts of the powder water reducer, 8 parts of the liquid water reducer, 1.6 parts of the defoamer, 2.4 parts of the retarder, 0.6 parts of the thickener, 8 parts of the polypropylene fiber, and 215 parts of the water in parts by mass;

[0053] Wherein, the silicate cement is PⅡ52.5 cement; the fly ash is first-grade fly ash with an activity of 120%; the SiO 2 The mass ratio of the composite hollow microspheres is ≥96%, the average particle size of the silica fume is 0.1-0.15 μm; the composite hollow microspheres include first hollow microspheres with a particle size of 75-100 μm, second hollow microspheres with a particle size of 100-150 μm, and third hollow microspheres with a particle size of 150-250 μm, wherein the mass ratio of the first hollow microspheres, the second hollow microspheres, and the third hollow microspheres is 2:5:3; the composite proppant includes a first ceramsite with a mesh size of 20-40, a second ceramsite with a mesh size of 40-70 and a third expanded clay with a mesh size of 70-140, wherein the mass ratio of the first expanded clay, the second expanded clay and the third expanded clay is 2:4:4; the fineness modulus of the sea sand is 2.5, and the particle size is <5mm; the powder water reducer is Sika 325C; the liquid water reducer is Hongqiang JSM3; the defoamer is P803, the retarder is tartaric acid; the thickener is T400; the length of the polypropylene fiber is 15-25mm, the tensile strength is >500Mpa, and the elastic modulus is >4500Mpa.

[0054] The silicate cement, the sulphoaluminate cement, the fly ash, the silica fume, the gypsum, the composite hollow microspheres, the composite proppant, the sea sand and the powder water reducing agent are added into a dry mortar mixer, and stirred at a uniform speed for 17.5 minutes to obtain a mixed dry material; the mixed dry material is added into a concrete mixer, and stirred at a uniform speed for 1.5 minutes; the liquid water reducing agent, the defoamer, the retarder, the thickener and the water are added, and stirred at a uniform speed for 6.5 minutes; the polypropylene fiber is added, and stirred at a uniform speed for 2.5 minutes to obtain the mixed slurry; the mixed slurry is vibrated and formed and cured to obtain the sea sand mortar.

[0055] After testing, the density of the sea sand mortar is 1628kg / m 3 , 28d compressive strength is 85.4Mpa, and shrinkage rate is 0.023%.

[0056] Embodiment 2

[0057] Weigh 340 parts of the silicate cement, 445 parts of the sulphoaluminate cement, 130 parts of the fly ash, 80 parts of the silica fume, 20 parts of the gypsum, 158 parts of the composite hollow microspheres, 200 parts of the composite proppant, 380 parts of the sea sand, 2.5 parts of the powder water reducer, 6.7 parts of the liquid water reducer, 1.8 parts of the defoamer, 2.2 parts of the retarder, 0.7 parts of the thickener, 9 parts of the polypropylene fiber, and 235 parts of the water in parts by mass;

[0058] Wherein, the silicate cement is PⅡ52.5 cement; the fly ash is first-grade fly ash with an activity of 120%; the SiO 2 The mass ratio of the composite hollow microspheres is ≥96%, the average particle size of the silica fume is 0.1-0.15 μm; the composite hollow microspheres include first hollow microspheres with a particle size of 75-100 μm, second hollow microspheres with a particle size of 100-150 μm, and third hollow microspheres with a particle size of 150-250 μm, wherein the mass ratio of the first hollow microspheres, the second hollow microspheres, and the third hollow microspheres is 2:5:3; the composite proppant includes a first ceramsite with a mesh size of 20-40, a second ceramsite with a mesh size of 40-70 and a third expanded clay with a mesh size of 70-140, wherein the mass ratio of the first expanded clay, the second expanded clay and the third expanded clay is 2:4:4; the fineness modulus of the sea sand is 2.5, and the particle size is <5mm; the powder water reducer is Sika 325C; the liquid water reducer is Hongqiang JSM3; the defoamer is P803, the retarder is tartaric acid; the thickener is T400; the length of the polypropylene fiber is 15-25mm, the tensile strength is >500Mpa, and the elastic modulus is >4500Mpa.

[0059] The silicate cement, the sulphoaluminate cement, the fly ash, the silica fume, the gypsum, the composite hollow microspheres, the composite proppant, the sea sand and the powder water reducing agent are added into a dry mortar mixer, and stirred at a uniform speed for 17.5 minutes to obtain a mixed dry material; the mixed dry material is added into a concrete mixer, and stirred at a uniform speed for 1.5 minutes; the liquid water reducing agent, the defoamer, the retarder, the thickener and the water are added, and stirred at a uniform speed for 6.5 minutes; the polypropylene fiber is added, and stirred at a uniform speed for 2.5 minutes to obtain the mixed slurry; the mixed slurry is vibrated and formed and cured to obtain the sea sand mortar.

[0060] After testing, the density of the sea sand mortar is 1682kg / m 3 , 28d compressive strength is 88.6Mpa, and shrinkage rate is 0.018%.

[0061] Embodiment 3

[0062] Weigh 318 parts of the silicate cement, 475 parts of the sulphoaluminate cement, 150 parts of the fly ash, 70 parts of the silica fume, 35 parts of the gypsum, 146 parts of the composite hollow microspheres, 225 parts of the composite proppant, 415 parts of the sea sand, 3 parts of the powder water reducer, 6 parts of the liquid water reducer, 2 parts of the defoamer, 2 parts of the retarder, 0.85 parts of the thickener, 12 parts of the polypropylene fiber, and 205 parts of the water in parts by mass;

[0063] Wherein, the silicate cement is PⅡ52.5 cement; the fly ash is first-grade fly ash with an activity of 120%; the SiO 2 The mass ratio of the composite hollow microspheres is ≥96%, the average particle size of the silica fume is 0.1-0.15 μm; the composite hollow microspheres include first hollow microspheres with a particle size of 75-100 μm, second hollow microspheres with a particle size of 100-150 μm, and third hollow microspheres with a particle size of 150-250 μm, wherein the mass ratio of the first hollow microspheres, the second hollow microspheres, and the third hollow microspheres is 2:5:3; the composite proppant includes a first ceramsite with a mesh size of 20-40, a second ceramsite with a mesh size of 40-70 and a third expanded clay with a mesh size of 70-140, wherein the mass ratio of the first expanded clay, the second expanded clay and the third expanded clay is 2:4:4; the fineness modulus of the sea sand is 2.5, and the particle size is <5mm; the powder water reducer is Sika 325C; the liquid water reducer is Hongqiang JSM3; the defoamer is P803, the retarder is tartaric acid; the thickener is T400; the length of the polypropylene fiber is 15-25mm, the tensile strength is >500Mpa, and the elastic modulus is >4500Mpa.

[0064] The silicate cement, the sulphoaluminate cement, the fly ash, the silica fume, the gypsum, the composite hollow microspheres, the composite proppant, the sea sand and the powder water reducing agent are added into a dry mortar mixer, and stirred at a uniform speed for 17.5 minutes to obtain a mixed dry material; the mixed dry material is added into a concrete mixer, and stirred at a uniform speed for 1.5 minutes; the liquid water reducing agent, the defoamer, the retarder, the thickener and the water are added, and stirred at a uniform speed for 6.5 minutes; the polypropylene fiber is added, and stirred at a uniform speed for 2.5 minutes to obtain the mixed slurry; the mixed slurry is vibrated and formed and cured to obtain the sea sand mortar.

[0065] After testing, the density of the sea sand mortar is 1590kg / m 3 , 28d compressive strength is 82.3Mpa, and shrinkage rate is 0.015%.

[0066] Although the preferred embodiments of the present application have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present application.

[0067] Finally, it should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or terminal device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or terminal device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or terminal device including the elements.

[0068] The above is a detailed introduction to a lightweight, low-shrinkage, high-strength sea sand mortar and a preparation method thereof provided by the present application. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for general technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A lightweight, low shrinkage and high strength sea sand mortar, characterized in that: The invention comprises, by weight, 250-350 parts of silicate cement, 300-480 parts of sulphoaluminate cement, 100-200 parts of fly ash, 50-100 parts of silica fume, 100-200 parts of composite hollow microspheres, 200-300 parts of composite proppant, 300-450 parts of sea sand, 5-15 parts of admixture and 200-260 parts of water; wherein the composite hollow microspheres comprise first hollow microspheres with a particle size of 75-100 μm, second hollow microspheres with a particle size of 100-150 μm, and a third hollow microsphere with a particle size of 150-250 μm, wherein the mass ratio of the first hollow microsphere, the second hollow microsphere and the third hollow microsphere is (1-3): (4-6): (2-4); the composite proppant comprises a first ceramsite with a mesh size of 20-40, a second ceramsite with a mesh size of 40-70 and a third ceramsite with a mesh size of 70-140, wherein the mass ratio of the first ceramsite, the second ceramsite and the third ceramsite is (1-3): (3-5): (3-5).

2. The sea sand mortar according to claim 1, characterized in that: The composite hollow microspheres are sintered at 1400°C.

3. The sea sand mortar according to claim 1, characterized in that: The mass proportion of spherical particles in the fly ash is greater than 95%, wherein the mass proportion of the spherical particles with a particle size of ≤1 μm is greater than 90%.

4. The sea sand mortar according to claim 1, characterized in that: The admixtures include a water reducer, a defoamer, a retarder and a thickener; the water reducer includes a powder water reducer and a liquid water reducer, wherein the mass ratio of the powder water reducer to the liquid water reducer is (1-3): (14-16).

5. The sea sand mortar according to claim 1, characterized in that: Calculated by weight, it also includes: 20-50 parts of gypsum.

6. The sea sand mortar according to claim 1, characterized in that: Calculated by weight, it also includes: 5-12 parts of polypropylene fiber.

7. The sea sand mortar according to claim 6, characterized in that: The length of the polypropylene fiber is 15-25 mm, the tensile strength is greater than 500 MPa, and the elastic modulus is greater than 4500 MPa.

8. A method for preparing sea sand mortar according to any one of claims 1 to 4, characterized in that: include: Put the silicate cement, the sulphoaluminate cement, the fly ash, the silica fume, the composite hollow microspheres, the composite proppant, the sea sand and the dry components of the admixture into a dry mortar mixer, and stir at a constant speed for 15-20 minutes to obtain a mixed dry material; Put the mixed dry materials into a concrete mixer, stir at a constant speed for 1-2 minutes, add the aqueous component in the admixture and the water, stir at a constant speed for 5-8 minutes, and obtain a mixed slurry; The mixed slurry is vibrated into shape and cured to obtain the sea sand mortar.